What the dental practitioner needs to know about pharmaco-therapeutic modalities of COVID-19 treatment: A review (2020)
Background/purpose: Several pharmacotherapeutic methods have been used for the treatment of COVID-19 with varying degrees of success. No definitive treatment or vaccine has been officially approved to-date. This review aimed to highlight COVID-19 pharmacotherapeutic agents that are relevant to dental practice in terms of their clinical indications in COVID-19 and dental practice, as well as their adverse effects as they impact the dental patient. Material and methods: Systematic search was performed using the following keywords combinations: Pharmacotherapy AND COVID-19 OR Pharmacotherapy AND SARS-CoV-2 OR Treatment AND COVID-19. Studies were categorized according to the type of pharmacotherapy used. Pharmacotherapeutic agents were extracted and only those relevant to dental practice were included for review. Results: For analysis, a total of 79 clinical trials research articles were included that included COVID-19 pharmacotherapeutic agents relevant to dental practice. Those were analgesics (paracetamol; non-steroidal anti-inflammatory agents); antibiotics (azithromycin, doxycycline, metronidazole); antivirals (penciclovir); and immunomodulatory agents (hydroxychloroquine, corticosteroids). While some COVID-19 drugs are less relevant to dental practice, as antivirals and hydroxychloroquine, their association with long-term adverse effects requires adequate knowledge among dental practitioners. Conclusion: Many of COVID-19 pharmacotherapeutic agents are used to treat oral diseases particularly orofacial pain and inflammatory conditions. Furthermore, some of these drugs may induce adverse effects that complicate dental treatment. Thorough knowledge of COVID-19 therapy and its dental implications is essential for dental practitioners, and is expected to contribute to a better understanding and effective utilization of these therapeutic agents.